PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA DHARMAWACANA - Gede Agus Jaya Negara; I Nyoman Buda Asmara Putra (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2020)
The development of information and communication technology is developing very rapidly, almost all people of the world are now addicted to technology that is very indulgent, it cannot be denied that the presence of information and communication technology has an impact on religious activities that cause changes to the way of carrying out Hindu or dharmawacana information. What used to be done by face to face, but now can be done by utilizing the presence of social media. The presence of social media makes people who want to watch, listen to dharmawacana can be done wherever they want. The important thing is they have the tools to use social media applications. Likewise for pendharmawacana can now utilize this technology to spread Hindu teachings more widely without being limited by space and time.Keywords: Social Media, Dharmawacana Media